Pengaruh Diaphragmatic Breathing dan Endurance Exercise Terhdap Peningkatan Kapasitas Kardiorespirasi Pada Pasien Hospital-Acquired Pneumonia - Azzahra, Alifia; Puspitarani, Annisya; Sativani, Zahra; Pahlawi, Riza (UI Scholars Hub, 2022)
The purpose of this case study is to determine the effect of diaphragmatic breathing and endurance exercise in hospital-acquired pneumonia (HAP) cases. HAP is a nosocomial pneumonia that occurs 48 hours or more after the patient is admitted to the hospital, without any signs of pulmonary infection at the time of initial treatment. The existence of clinical manifestations that appear, patients with HAP tend to avoid physical activity which can decrease the functional capacity of the respiratory system and have an impact on decreasing endurance. Diaphragmatic breathing exercise is thought to be able to help reduce shortness of breath, reduce the work of the accessory muscles of breathing, improve breathing frequency and also improve breathing patterns. Endurance training aims to increase the stimulation of the cardiorespiratory system response so that oxygen transportation becomes more efficient and the patient is able to carry out optimal activities. The method used in this case study is an evidence-based case report with a clinical question,